Hall and Ion-Slip Current Effects on Micropolar Fluid Flow Over a Vertical Plate with an Inclined Magnetic Field - Islam, Mohammad Rafiqul; Nasrin, Sonia (European Journal of Applied Sciences, 2024)
In this study, we explore how Hall and Ion-slip currents influence the flow of micropolar fluid over a vertical plate in the presence of an inclined magnetic field. To simplify the analysis, we consider a small magnetic Reynolds number, allowing us to exclude the magnetic induction equation. The equations governing the flow are derived from principles of linear momentum equation, angular momentum equation, and energy equation which are made dimensionless through similarity analysis. Then these non-linear, dimensionless equations are solved by using the explicit finite difference method for finding the primary velocity, secondary velocity, microrotation, and temperature. This investigation extensively examines the impact of key parameters on velocity, microrotation, and temperature distributions. It also provided concise graphical explanations of skin friction and heat transfer rate at the plate.